2015
DOI: 10.3923/jp.2015.142.150
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Toxoplasma gondii (Apicomplexa: Sarcocystidae) in the Brown Dog Tick Rhipicephalus sanguineus (Acari: Ixodidae) Fed on Infected Rabbits

Abstract: The brown dog tick Rhipicephalus sanguineus is a three-host tick that feeds primarily on dog and occasionally on other hosts, including human. Toxoplasmosis is generally considered the most important disease that causing abortion of both pregnant women and different female animals throughout the world. Therefore, the aim of this study was to determine the ability of the brown dog tick R. sanguineus to acquire Toxoplasma infection through feeding its larvae on experimentally infected rabbits with T. gondii. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Alimentary way of transmission does not clarify a high prevalence of T. gondii in many of herbivorous mammals (up to 75%) [37,38], wild rodents (up to 35%) [39,40] and fowl (even up to 100%) [41], which should have limited contact with the invasive forms of this protozoan. For this reason, other ways of T. gondii transmission are considering, including -by blood-sucking arthropods [42][43][44]. Deryło et al [45] as the first showed the experimental transmission of T. gondii in I. ricinus, when they found tachyzoites and bradyzoites in tissues of nymphs and females of this tick species.…”
Section: Discussionmentioning
confidence: 99%
“…Alimentary way of transmission does not clarify a high prevalence of T. gondii in many of herbivorous mammals (up to 75%) [37,38], wild rodents (up to 35%) [39,40] and fowl (even up to 100%) [41], which should have limited contact with the invasive forms of this protozoan. For this reason, other ways of T. gondii transmission are considering, including -by blood-sucking arthropods [42][43][44]. Deryło et al [45] as the first showed the experimental transmission of T. gondii in I. ricinus, when they found tachyzoites and bradyzoites in tissues of nymphs and females of this tick species.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that sporulated oocysts of Toxoplasma spp. can persist and survive in the environment for a long time and can infect all warm-blooded animals, birds, and humans (Frenkel, 2000;Sibley et al, 2009;Abdel-Shafy et al, 2015). Oocysts require 1 to 5 days to sporulate and become infective.…”
Section: The Protozoon Parasitementioning
confidence: 99%